Post-traumatic cerebrospinal fluid nasal leak. Results of the implementation of a work protocol.: https://doi.org/10.59156/revista.v37i02.495 - Ulloque Caamaño, Liezel; Villalonga, Juan F.; Zúñiga, Alexander J.; Romero-Leguina, Benjamín; Aiquel, Luis F.; Campero, Álvaro (Revista Argentina de Neurocirugía, 2023)
Introduction: Patients with anterior skull base fractures after TBI have a high risk of presenting cerebrospinal fluid leak (CFL) through the nostrils. Timely and appropriate management is important to avoid complications. The “HP protocol” for surgical treatment was developed. Objective: Show the results of the application of the HP protocol. Materials and methods: Retrospective cross-sectional study, patients ≥ 15 years old with a diagnosis of post- TBI nasal CFL, from 1/1/2016 to 8/31/2021 who were admitted to the hospital and required repair surgery. Included 28 patients. p value ˂0.05 was statistically significant. Results: 96.4% men, mostly young adults with mild TBI. 82.1% presented early CFL. All required frontal transcranial repair, in 67.9% it was bilateral. Repair before 7 days was in 39.3%, 7-21 days in 46.4%, and after 21 days in 14.3%. Use of DLC: preoperative 10.7%, intraoperative 60.7%, postoperative 46.4%. In 89.3%, the location of the intraoperative CFL was consistent with the CT scan. Since 2020, the management of the CFL has been systematized. The recurrence was 10.7% before 2020, after which it was 0 and was associated with low Glasgow, onset of CFL 7 days after TBI (p<0.05). Found complications: meningitis 28.6%, seizure 25%, tension pneumocephalus 7.1%, abscess 3.6%, anosmia 14.3%. CFL mortality: 3.6%. Cure 96.4%. Conclusions: The application of the HP Protocol had satisfactory results. The post-TBI nasal CFL recurrence rate was 0%.